Pumps for microfluidic cell culture. Issue 2 (1st October 2013) - Byun, Chang Kyu; Abi‐Samra, Kameel; Cho, Yoon‐Kyoung; Takayama, Shuichi; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> In comparison to traditional in vitro cell culture in Petri dishes or well plates, cell culture in microfluidic‐based devices enables better control over chemical and physical environments, higher levels of experimental automation, and a reduction in experimental materials. Over the past decade, the advantages associated with cell culturing in microfluidic‐based platforms have garnered significant interest and have led to a plethora of studies for high throughput cell assays, organs‐on‐a‐chip applications, temporal signaling studies, and cell sorting. A clear concern for performing cell culture in microfluidic‐based devices is deciding on a technique to deliver and pump media to cells that are encased in a microfluidic device. In this review, we summarize recent advances in pumping techniques for microfluidic cell culture and discuss their advantages and possible drawbacks. The ultimate goal of our review is to distill the large body of information available related to pumps for microfluidic cell culture in an effort to assist current and potential users of microfluidic‐based devices for advanced in vitro cellular studies.